The Specifics of the Perception of the Names of Colours in the Language World Model of English-speaking Middle-aged Representatives - Савчук, Еліна Олександрівна; Галунова, Наталія Миколаївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
The article deals with the general concept of the language world model, the peculiarities of its formation and functioning throughout historical development of humanity. Special attention is paid to the linguistic conceptualization of the colour perception of the surrounding reality of separate individuals, depending on their ethnicity. The article analyses specifics of the functioning of the lexical block of the names of colours in language world model typical of English-speaking middle-aged representatives. Basing on the collected material, a qualitative and quantitative analysis was conducted. The main types of associations are identified, the emotional and evaluative components of the reactions are analyzed, respective generalizations and conclusions are made.